Complementary Therapy to Treat Back Pain in Pregnant Women: Literature Review - Malia, Anna (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Back pain during pregnancy is one of the discomforts that pregnant women often complain about. Even though it is not a serious problem during pregnancy, it can have a negative impact on the quality of life of pregnant women. This study aims to examine complementary care services from several studies that can be provided to pregnant women to treat lower back pain, especially in the third trimester. Method: The method used is to review research related to providing complementary care to pregnant women who complain of back pain in pregnant women. Conclusion: There are 4 complementary methods that can be used to reduce back pain, namely, acupressure techniques, endorphin massage, pelvic rocking, and pregnancy exercises.